Motion Illusions in Optical Art Presented for Long Durations are Temporally Distorted. (July 2013) - Nather, Francisco Carlos; Mecca, Fernando Figueiredo; Bueno, José Lino Oliveira
Static figurative images implying human body movements observed for shorter and longer durations affect the perception of time. This study examined whether images of static geometric shapes would affect the perception of time. Undergraduate participants observed two Optical Art paintings by Bridget Riley for 9 or 36 s (group G9 and G36, respectively). Paintings implying different intensities of movement (2.0 and 6.0 point stimuli) were randomly presented. The prospective paradigm in the reproduction method was used to record time estimations. Data analysis did not show time distortions in the G9 group. In the G36 group the paintings were differently perceived: that for the 2.0 point one are estimated to be shorter than that for the 6.0 point one. Also for G36, the 2.0 point painting was underestimated in comparison with the actual time of exposure. Motion illusions in static images affected time estimation according to the attention given to the complexity of movement by the observer, probably leading to changes in the storage velocity of internal clock pulses.